2019
DOI: 10.21470/1678-9741-2018-0426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Depression and Anxiety in Coronary Artery Bypass Surgery Patients: A Prospective Clinical Study

Abstract: Objective The aim of this clinical study is to determine the depression and anxiety levels in coronary artery bypass graft (CABG) surgery patients in the pre and postoperative periods. Methods This clinical prospective study was done with 65 patients. Beck’s Depression Inventory (BDI) and Beck’s Anxiety Inventory (BAI) tests were performed in patients who had a diagnosis of coronary artery disease and were awaiting CABG surgery. These patients presented characteristic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 23 publications
0
21
0
8
Order By: Relevance
“…Another large study in 514 German CAD patients, evaluated by the Mini International Neuropsychiatric Interview and the Global Assessment of Functioning (GAF) scale demonstrated comorbidity of depression with CAD and treatment of the depression resulted in improvement of this condition [26]. Interestingly, patients undergoing CABG operation, depression and anxiety were increased after the operation compared to the pre-operative period [27]. Evaluation of our results according to sex, demonstrated predominance of men rather than women as having abnormal MPI and thus CAD (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Another large study in 514 German CAD patients, evaluated by the Mini International Neuropsychiatric Interview and the Global Assessment of Functioning (GAF) scale demonstrated comorbidity of depression with CAD and treatment of the depression resulted in improvement of this condition [26]. Interestingly, patients undergoing CABG operation, depression and anxiety were increased after the operation compared to the pre-operative period [27]. Evaluation of our results according to sex, demonstrated predominance of men rather than women as having abnormal MPI and thus CAD (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of authors observed a positive impact on depression prevalence and levels after surgery, as well as in the short and medium term, although others found that these levels increased after surgery [28,32,33,48,49,55,57,89].…”
Section: Levels Of Depression Before and After Cabg Surgery And Follomentioning
confidence: 99%
“…Post-surgery, most authors report normal levels, while others found mild [28,36,49,53,58,60,66,83,85,88], moderate [27,47,69], and severe [32] levels.…”
Section: Levels Of Depression Before and After Cabg Surgery And Follomentioning
confidence: 99%
“…The active involvement of parents in caring for their infants is one of the best and most effective ways to reduce parental stress [7]. Support of parents is in line with family-centered care and aims to enable them to play their parental roles and support them in stressful situations [8]. Therefore, different organizations should support the parents to positively influence and promote infant health [3].…”
Section: Introductionmentioning
confidence: 99%